Application of iREITs in developing WAQF assets: alternative and mechanism - Ramlee, Roslily; Che Embi, Nor Azizan; Mohamed Sultan, Syed Alwi (2015)
This paper attempts to explore the possibility of using Islamic real estate investment trusts (I-REITs) as one of the potential funding method for waqf assets development. This paper illustrates an alternative I-REITs model and mechanism to raise funding from capital market for Waqf assets development. This model is applicable to religious councils that have no existing property to back the issuance of I-REITs. The fund raising process is done through two phases. The first phase is the incubation stage whereby Mutawalli issues Cash Waqf certificates under Mudharabah or Wakalah structures to allow fund mobilization towards development/acquiring of the Waqf properties. The second phase is the disposal of Waqf properties to I-REITs through ijarah contract. The funds raised by the issuance of I-REITs is not only meant to fund the initial stage of waqf development but are also expected to generate continuous cash inflows to the State Islamic Religious council (SIRC).